Analysis of the distribution of the Grison (Galictis vittata) (Carnivora: Mustelidae) in the Colombian Caribbean - Jiménez-Alvarado, Juan Sebastián; Arias-Ocampo, Angélica; Pineda-Guerrero, Alexandra; Zárrate-Charry, Diego A; Vela-Vargas, I. Mauricio; Chacón-Pacheco, Julio; González-Maya, José F. (THERYA, 2015)
The Grison (Galictis vittata) is a mustelid carnivore with a wide distribution in the American continent, including Colombia. However, is one of the less studied carnivore species in Colombia, with scarce information regarding distribution, ecology and conservation status. We compiled all records and observations available for the species in the Caribbean region of Colombia. Additionally, through field work held throughout the region, we present new confirmed records for the species. We obtained a total of 78 records, distributed in seven of the eight departments of the Caribbean Region of Colombia; of these, 54 records are new for the region and are located in five departments. The new records expand the known distribution of the species in 162 km to the South and 36,500 km2 in extent from its previously estimated distribution, also confirming its presence in three departments for the first time. Our results extend the knowledge of the species for the Caribbean region of Colombia by providing new records and data on distribution and extending its known range. These results also highlight the need for further study of the species regarding most aspects of its natural history.